2021
DOI: 10.1159/000517005
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Cytology versus Core-Needle Biopsy for Breast Lesions: A Dilemma of Superiority between the Two

Abstract: <b><i>Introduction:</i></b> Core-needle biopsy (CNB) is a minimally invasive procedure used in preoperative diagnosis of breast lumps. It has been seen that in few years, the CNB seems to be replacing the fine-needle aspiration cytology (FNAC), although no study had yet conclusively proved a superiority of one over the other. <b><i>Aims and Objectives:</i></b> The aim of this study was to study the cytohistological spectrum of palpable breast lesions and to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…FNAC is cost-effective, minimally invasive and can be performed in the clinic setting. 14,28 Ancillary testing which could improve the diagnostic accuracy of FNAC is critical to a public health screening program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FNAC is cost-effective, minimally invasive and can be performed in the clinic setting. 14,28 Ancillary testing which could improve the diagnostic accuracy of FNAC is critical to a public health screening program.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pre-analytical delays can influence the performance of adjunctive testing modalities like IHC and FISH. FNAC is cost-effective, minimally invasive and can be performed in the clinic setting 14,28 . Ancillary testing which could improve the diagnostic accuracy of FNAC is critical to a public health screening program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, CNB was performed on older patients, while FNA and submission for cytology were performed on younger patients. This may be explained by clinicians having a higher clinical suspicion of breast carcinoma in older patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the present study, a much lower agreement between CNB and FNAC was reported by Tikku and Umap who found this agreement in 58/107 (54.2%) cases only [ 14 ]. Verma et al in their study assessed the agreement for different corresponding cytological and biopsy categories and found it to range from poor (C1) to near-perfect (C2) [ 20 ]. In another study, Siddavatan et al found a moderate concordance between FNAC and CNB, similar to the present study [ 16 , 21 ].…”
Section: Discussionmentioning
confidence: 99%